Group learning capacity: the roles of open-mindedness and shared vision - Lord, Mimi (Frontiers in Psychology, 2015)
Open-mindedness is a construct that is considered a key foundational aspect of learning in individuals, groups and organizations. Also known as critical inquiry or reflection, open-mindedness is believed to increase learning through examination of prior beliefs, decisions and mistakes, and also through openness to new ideas. Renowned theorists including Dewey and Argyris have emphasized the relationship between open-mindedness and learning, yet little quantitative research has tested it or examined moderators of the linkage. The setting for the current study is that of endowment investment committees at U.S. universities and colleges who need to make knowledgeable and well-reasoned decisions about the composition of investment portfolios. Findings indicate that open-mindedness has a positive, significant effect on group learning capacity and also that shared vision, which represents the group’s collective purpose and direction, moderates that relationship. The literature review and discussion offer insights about how open-mindedness is related to the research on group conflict, and how shared vision differs from concepts such as interpersonal cohesiveness and conformity that have been associated with groupthink. A review of relevant research from the fields of organizational learning, group dynamics, and absorptive capacity provides context for the development of the hypotheses and the discussion of findings.